Combined Therapy for Patients after Ischemic Stroke as a Support of Social Adaptability - Vostrý, Michal; Fischer, Slavomil; Cmorej, Patrik Christian; Nesvadba, Marcel; Peran, David; Šín, Robin (Neuro endocrinology letters, 2019)
THE OBJECTIVE: The main objective of the research was to find out the effectivity of the combined therapy suitable for patients after ischemic stroke (promoting social adaptability). The therapy itself is then focused on robotic, psychomotor and cognitive therapy. The research indicators were divided into three categories of psychological, social and cognitive indicators. PROBAND SAMPLE: We have a 58 probands diagnosed with a stroke participated on the research (ischemic type I60-I69; ICD-10; the 10th revision of the International Statistical Classification of Diseases and Related Health Problem), out of which 49 were male patients ages between 48-55 and women between the age of 45-51. The data collection was then done during 2018. Indicators were evaluated and tested firstly after the initiation of the combined therapy, then after 10 weeks of intensive therapy, which took place 3 times a week 45 minutes for each patient participating in the research. RESULTS: The results of the research point to the fact, that combined therapy of robotic, psychomotor and cognitive can have positive effect on, and be suitable as a treatment for patients after ischemic stroke, regarding their productive age. Positive results have been therefore overt among all tested areas. CONCLUSION: The results of the research point to the fact, that combined therapy of robotic, psychomotor and cognitive can have positive effect on, and be suitable as a treatment for patients after ischemic stroke, regarding their productive age. Positive results have been therefore overt among all tested areas.
Keywords: kognitivně behaviorální terapie; Stroke Rehabilitation; fyzická vytrvalost; Female; kombinovaná terapie; techniky fyzikální terapie; Exoskeleton Device; ženské pohlaví; cévní mozková příhoda; lidé; Activities of Daily Living; Physical Therapy Modalities; Affect; Stroke; afekt; ischemie mozku; sociální přizpůsobení; rehabilitace po cévní mozkové příhodě; Social Adjustment; Physical Endurance; činnosti denního života; Male; exoskeleton; Combined Modality Therapy; Brain Ischemia; lidé středního věku; mužské pohlaví; Middle Aged; Cognitive Behavioral Therapy; Humans